Evaluation of the information given to patients undergoing head and neck cancer surgery using the EORTC QLQ-INFO25 questionnaire: A prospective multicentric study. (November 2016) - Bozec, Alexandre; Schultz, Philippe; Gal, Jocelyn; Chamorey, Emmanuel; Chateau, Yann; Dassonville, Olivier; Poissonnet, Gilles; Santini, José; Peyrade, Frédéric; Saada, Esma; Guigay, Joël; Benezery, Karen; et al.
Abstract: Aim: Providing head and neck cancer patients with adequate information is essential to their confidence and satisfaction regarding medical care. The aims of this study were to evaluate patient perceptions of the information received, the predictive factors of such perceptions and their potential correlation with patient quality of life (QoL). Methods: We conducted a prospective multicentric study using the European Organization for Research and Treatment of Cancer (EORTC) QLQ-INFO25 and QLQ-C30 questionnaires before and after surgery. Results: This study enrolled 200 patients, 149 men and 51 women, mean age 63.5 ± 10.3 years. Before and after treatment, global QLQ-INFO25 scores were 39.3 and 42.5, respectively, whereas satisfaction with the information received scores were 69.9 and 58.1, respectively. Regarding EORTC QLQ-INFO25 scores, between the pre- and post-treatment periods, we observed a significant increase in three scales/items (information about other services, information about different places of care and information about things you can do to help yourself) and a significant decrease in two scales/items (satisfaction with the information received and overall the information has been helpful). Before and after treatment, global QoL scores were 62.7 and 61.0, respectively. Overall, we found low correlations between QLQ-INFO25 and QLQ-C30 scores. Patient age and education level, centre of care, tumour site and treatment characteristics had a significant impact on QLQ-INFO25 scores. Conclusion: Perceived information was satisfactory in the perioperative period for head and neck cancer patients. Several demographic and clinical factors were identified as significant predictors of QLQ-INFO25 scores. Highlights: The European Organization for Research and Treatment of Cancer information module can be used for head and neck cancer patients. Perceived information was satisfactory in the perioperative period. Significant changes in QLQ-INFO25 scores can be observed before and after surgery. Demographic and clinical predictive factors of QLQ-INFO25 scores can be found.